The Heat Shock Protein 70 Family of Chaperones Regulates All Phases of the Enterovirus A71 Life Cycle - Su, Yu-Siang; Hsieh, Pei-Yu; Li, Jun-Syuan; Pao, Ying-Hsuan; Chen, Chi-Ju; Hwang, Lih-Hwa (Frontiers in Microbiology, 2020)
Enterovirus A71 (EV-A71) is one of the major etiologic agents causing hand, foot and mouth disease in children and occasionally causes severe neurological diseases or even death. EV-A71 replicates rapidly in host cells. For a successful infection, viruses produce large quantities of viral proteins in a short period, which requires cellular chaperone proteins for viral protein folding and viral particle assembly. In this study, we explored the roles of the heat shock protein 70 (HSP70) chaperone subnetwork in the EV-A71 life cycle. Our results revealed that EV-A71 exploits multiple HSP70s at each step of the viral life cycle, i.e., viral entry, translation, replication, assembly and release, and that each HSP70 typically functions in several stages of the life cycle. For example, the HSP70 isoforms HSPA1, HSPA8 and HSPA9 are required for viral entry and the translational steps of the infection. HSPA8 and HSPA9 may facilitate folding and stabilize viral proteins 3D and 2C, respectively, thus contributing to the formation of a replication complex. HSPA8 and HSPA9 also promote viral particle assembly, whereas HSPA1 and HSPA8 are involved in viral particle release. Because of the importance of various HSP70s at distinct steps of the viral life cycle, an allosteric inhibitor, JG40, which targets all HSP70s, significantly blocks EV-A71 infection. JG40 also blocks the replication of several other enteroviruses, such as coxsackievirus (CV) A16, CVB1, CVB3 and echovirus 11. Thus, targeting HSP70s may be a means of providing broad-spectrum antiviral therapy.